How many runners with new-onset Achilles tendinopathy develop persisting symptoms? A large prospective cohort study - Lagas, I. F.; Fokkema, T.; Bierma-Zeinstra, S. M. A.; Verhaar, J. A. N.; van Middelkoop, M.; de Vos, R.-J. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Background: Achilles tendinopathy (AT) occurs in half of the elite runners. AT is a difficult-to-treat tendon disease, which may progress from new onset to a chronic state. It is unknown how many runners with new-onset AT develop persisting symptoms and which prognostic factors are associated with this course. Objective: To describe how many runners develop persisting symptoms 1 year after onset of reactive AT. Study Design: Prospective cohort study. Methods: Runners registering for a Dutch running event (5-42.2 km) were eligible for inclusion. Runners reporting new-onset AT between registration for the running event and 1 month after received a 1-year follow-up questionnaire. The 1-year follow-up questionnaire inquired about persisting symptoms (yes/no), running activity, and metabolic disorders. We calculated the percentage of runners with persisting symptoms and performed a multivariable logistic regression analysis to study the association between potential prognostic factors and persisting symptoms. Results: Of 1929 participants, 100 runners (5%) reported new-onset AT. A total of 62 runners (62%) filled in the 1-year follow-up questionnaire. Persisting symptoms were reported by 20 runners (32%). A higher running distance per week before new-onset AT was associated with a lower risk of developing persisting symptoms (odds ratio (OR): 0.9, 95% confidence interval (CI): [0.9;1.0]). There was a positive trend toward an association between metabolic disorders and persisting symptoms (OR: 5.7, 95% CI: [0.9;36.2]). Conclusion: One third of runners develop persisting symptoms 1 year after new-onset AT. Interestingly, a higher running distance per week before new-onset AT potentially lowers the risk of developing persisting symptoms.